Microstructures of epidote-prehnite bearing damaged granitoids (northern Victoria Land, Antarctica): clues for the interaction between faulting and hydrothermal fluids. (June 2021) - Malatesta, Cristina; Crispini, Laura; Ildefonse, Benoit; Federico, Laura; Lisker, Frank; Läufer, Andreas
Abstract: Exhumed faults in granitoids along the Lanterman Fault-Rennick Graben Fault system (northern Victoria Land, Antarctica) show superposed ductile to brittle deformation and pervasive hydrothermal fluid-rock interaction. These processes triggered multiple brittle slip events producing crosscutting epidote and prehnite-rich fault veins, ultracataclasites and pseudotachylytes of crushing origin. Combined microstructural and minerochemical investigations on fault damage zones show three types of alteration: (i) albitization of K-feldspar and Ca-plagioclase; (ii) crystallization of prehnite and calcite in veins; (iii) alteration of magmatic phases by secondary hydrous minerals (e.g. chlorite, white mica, epidote and prehnite). The fault experienced various episodes of strain weakening and hardening, due to alteration of minerals and precipitation of epidote and prehnite within ultracataclastic intervals, at decreasing temperature conditions (200 < T°C < 450) and varying CO2 fugacity of the fluids. Cyclic crystallization of epidote/prehnite within the fault cores caused cementation and locking of faults, concentration of deformation at weaker horizons and a progressive broadening of the fault zone. Our results indicate that multiple co-seismic slip and syntectonic fluid flow very likely occurred prior to the Cenozoic brittle reactivation of inherited anisotropies in the northern Victoria Land crust along the Lanterman Fault-Rennick Graben Fault system and underlines its high potential for polyphasicity. Highlights: Exhumed faults in granitoids from Antarctica show multiple ductile to brittle shears. Syntectonic hydrothermal fluid-rock interaction processes affect slip history. Epidote and prehnite crystallization in fault rocks influence rheology.